Fikih Salat Gerhana Menurut Imam Ibnu Hajar Al-Haitami - Fahmi Fatwa Rosyadi Satria Hamdani; Encep Abdul Rojak; Maulan Rif’atul Wafy (University of Muhammadiyah Sumatera Utara, 2019)
The movement of the sun, the earth, and the moon on their each orbites have caused a natural fenomenon called an eclipse. Rasulullah SAW taught his followers to take a pray when this situation comes. Many 'ulamas have a different opinions in one or two case order to do the eclipse prayer, for example when the eclipse couldn't be seen because it hindered by clouds or if it's cloudy. One of the ulama's opinion which will be reviewed is the opinion of Ibnu Hajar al-Haitami. The aim of this research is to find out the fiqh of eclipse prayer in the study of Islamic Law, later Haitami's opinion concerning the implementation of eclipse prayer when it's cloudy. Qualitative approach used in this research with concept analysis, where researcher acumulate literatures that relates with the topic. The result of this reseach known that there are no significant differences in fiqh of eclipse prayer in the study of Islamic Law, but if it's cloudy when the eclipse happening, Haitami's argue that eclipse prayer keeps held when the eclipse happens before the cloudy. Meanwhile, if the cloudy happens from the begining to the last seconds of eclipse, the eclipse prayer not applied.